2003
DOI: 10.1002/app.12030
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the CaCO3 nanoparticles on the molecular orientation of the polypropylene matrix

Abstract: ABSTRACT:The presence of aggregates of CaCO 3 nanoparticles in an isotactic polypropylene matrix processed by extrusion promotes the apparition of residual stresses. These stresses are removed with a thermal treatment of the composite, but a higher molecular orientation is then produced. The chain orientation inside the sample is nonhomogeneous due to the presence of the aggregates of nanoparticles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
87
0
5

Year Published

2005
2005
2015
2015

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(93 citation statements)
references
References 18 publications
1
87
0
5
Order By: Relevance
“…[51][52][53] On the other hand, there are literature works stating that the presence of nanoparticles can modify the molecular orientation, the crystallization temperature, the crystallization degree, and the crystallization rate of the matrix of a nanocomposite. 54,55 Indeed, it has been reported that gold nanoparticles favor the crystalline orientation of L-alanine crystals preferentially along the c-axes. 56 On the basis of these observations, the scheme shown as inset (I) in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…[51][52][53] On the other hand, there are literature works stating that the presence of nanoparticles can modify the molecular orientation, the crystallization temperature, the crystallization degree, and the crystallization rate of the matrix of a nanocomposite. 54,55 Indeed, it has been reported that gold nanoparticles favor the crystalline orientation of L-alanine crystals preferentially along the c-axes. 56 On the basis of these observations, the scheme shown as inset (I) in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Este teste é comumente aplicado na caracterização de filmes poliméricos, utilizados no acondicionamento de produtos, que podem estar em contato com pontas, cantos vivos e outros tipos de protuberâncias capazes de danificar a embalagem durante o acondicionamento e a distribuição [7] . Para o ensaio da termossoldagem à tração, filmes de 25 cm de comprimento e 5 cm de largura foram selados, segundo norma ASTM D F88-00, empregando temperatura média de 165 °C e pressão de 3,5 kgf.cm -2 por 0,5 segundos.…”
Section: Preparação Das Amostrasunclassified
“…Estudos sobre nanocompósitos PP/argila organofílica são amplamente divulgados na literatura [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] . Entretanto, o número de publicações sobre filmes de nanocompósitos PP/argila organofílica para aplicação no setor de embalagens alimentícias é limitado [21][22][23] e a literatura tem mostrado que, ao contrário dos nanocompósitos preparados com matrizes polares como poliamidas, poliésteres e policarbonatos, os preparados com matrizes apolares poliolefínicas não tem apresentado melhoramentos significativos nas propriedades mecânicas e de barreira, o que tem sido atribuído a fraca adesão interfacial polímero/argila [20] .…”
Section: Introductionunclassified
“…Therefore, in order to obtain an indication of the size of these larger structures as well as their possible size variation with CN concentration, micro-Raman spectroscopy was employed. Micro-Raman spectroscopy was used in previous studies of polypropylene composites [33] as well as on its nanocomposites to detect the thermal residual strains and chain orientation [34][35][36]. In the present work, 2D…”
Section: Morphological Characterizationmentioning
confidence: 99%